Impact of Work From Home Policy on Behavior and Productivity of Lecturers and Education Staff - Afni Sirait; Sri Luna Murdianingrum (Research Synergy Foundation, 2021)
Policy Work From Home (WFH ) is enforce within the FEB UPN